Cystatin F Affects Natural Killer Cell Cytotoxicity - Perišić Nanut, Milica; Sabotič, Jerica; Švajger, Urban; Jewett, Anahid; Kos, Janko (Frontiers in Immunology, 2017)
Cystatin F is a cysteine peptidase inhibitor which, unlike other cystatin family members, is targeted to endosomal/lysosomal compartments. It is synthesized as an inactive disulphide-linked dimer which is then converted to an active monomer by proteolytic cleavage of 15 N-terminal residues. Cystatin F has been suggested to regulate the cytotoxicity of natural killer (NK) cells by inhibiting the major granzyme convertases, cathepsins C and H. To test this hypothesis, we prepared variants of cystatin F and analyzed their uptake, subcellular trafficking and peptidase inhibition, as well as their impact on the cytotoxicity of NK-92 cells and primary NK cells. The N-glycosylation pattern is responsible for the secretion, uptake and subcellular sorting of cystatin F in HeLa and Hek293 cells, whereas the legumain binding site had no effect on these processes. Active, N-terminally truncated, monomeric cystatin F can also be internalized by recipient cells and targeted to endo/lysosomes, affecting also cells lacking the activating peptidase. Cystatin F mutants capable of cell internalization and trafficking through the endo/lysosomal pathway significantly decreased cathepsin C and H activities, both in situ, following transfection and in trans, using conditioned media. Further, incubation of IL-2 stimulated NK-92 and primary NK cells with full length and N-terminally truncated cystatin F mutants led to suppression of their granule-mediated cytotoxicity. This effect was most significant with the N-terminally truncated mutants. These results suggest that cystatin F can be an important mediator within tumor microenvironment affecting the cytotoxicity of NK cells and consequently antitumour immune response.